2003
DOI: 10.1007/s11746-003-0834-6
|View full text |Cite
|
Sign up to set email alerts
|

Simulation modeling of the phase behavior of palm oil‐supercritical carbon dioxide

Abstract: The phase behavior of crude palm oil (CPO) with supercritical CO 2 was successfully modeled in an Aspen Plus ® 10.2.1 commercial simulator (Aspen Technology Inc., Cambridge, MA) using the Redlich-Kwong-Aspen (RKA) equation of state thermodynamic model. The modeling procedure involved estimating pure component vapor pressures and critical properties and computing a regression of phase equilibrium behavior. The interaction parameters for the RKA model were obtained from the regression of experimental phase equil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…Consequently, thermodynamic properties and vapor pressure or pure component parameters for Antoine equations are required, and must be established. The thermo-physical properties are introduced in the simulation in terms of physical properties such as boiling point (TB), critical temperature (TC), critical pressure (PC), acentric factor (ω) and liquid molar volume (Vl20) for each component, and can be seen in Table A1 in the Appendix, as accomplished by Lim et al [13]. Equation (2) refers to an extension of the Antoine equation from Lim et al's work, and its parameters are shown in Table 3.…”
Section: Vapor Pressure Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, thermodynamic properties and vapor pressure or pure component parameters for Antoine equations are required, and must be established. The thermo-physical properties are introduced in the simulation in terms of physical properties such as boiling point (TB), critical temperature (TC), critical pressure (PC), acentric factor (ω) and liquid molar volume (Vl20) for each component, and can be seen in Table A1 in the Appendix, as accomplished by Lim et al [13]. Equation (2) refers to an extension of the Antoine equation from Lim et al's work, and its parameters are shown in Table 3.…”
Section: Vapor Pressure Estimationmentioning
confidence: 99%
“…where S is sum of the squared error, m is the number of experimental data point within the temperature range of 373 K-503 K, P calc i is the calculated vapour pressure obtained from Lim et al's work [13] using Equation (2) and P exp i is the expected vapour pressure in Equation (3) (as available in ASPEN HYSYS). The pure component parameters for modified Antoine equation (Equation (3)) and coefficient of determination (R 2 ) of each component are summarized in Table 4.…”
Section: Vapor Pressure Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…The model predictions were also compared to the experimental VLE data presented in other literatures [1,19,23,26,27,29,30]. In addition, the phase equilibrium data were correlated with relatively simple PR-EOS using Wong-Sandler mixing rule.…”
Section: Introductionmentioning
confidence: 99%
“…Reliable high-pressure vapor-liquid equilibrium (VLE) data over a wide range of pressures and temperatures, and development of simple thermodynamic models provide basic, necessary information for the process development and economic evaluation of the extraction and the fractionation processes. Although many single component VLE data and modeling works are presented in open literature [15][16][17][18][19][20][21][22], only few works concerning multicomponent VLE data and thermodynamic modeling have been published [23][24][25][26]. In addition, some of these works are suffered from limited phase equilibria data at narrow temperature or pressure range, and complexity and low applicability of thermodynamic models.…”
Section: Introductionmentioning
confidence: 99%